REFLECTION OF LOCAL WISDOM ON WOMEN'S RIGHTS IN MINANGKABAU INDIGENOUS COMMUNITIES - Sri Yunarti; Muhammad Syakir; Desmita Desmita; Elfi Elfi (State Institute of Islamic Studies Batusangkar, 2021)
Women in Minangkabau traditional culture are Limpepeh Rumah Nan Gadang which are symbols of the existence of harmonization of households; guarantee of the quality of human resources both in terms of inheritance and descendants, and guarantee of knowledge and availability of family food. This research is conducted in the Minangkabau community within Luhak Nan Tuo area, particularly in the Tanah Datar Regency community. By using the interview method, it reflects three stages of women’s position in Minangkabau descriptively. These stages are (1) in decision making to determine assets in the family economy, (2) in the working distribution, and (3) in managing family finances. From the result of the study, it can be seen that the position of women in making decisions is still in the second position even though in the end the women who act as bundo kanduang are still being asked for opinions in terms of protecting reproductive health which indicated in decreasing point. There has been a change in working distribution in which the women are allowed to work not only in domestic sectors but also in public sectors. However, women’s position in managing family finances are getting decreased. This is as a result of culture and its values in structural, solidarity, existence of the society. Bundo kanduang institution in Nagari is the basis for empirical empowerment and local wisdom on women's rights. It is just a sub-section of the institution that deals with women's, social, children, youth and women's issues. The social reality where the domestication of discrimination has implications for women. There is still a strong gender bias of community leaders. At least, there are female figures who are able to act as agents for women's empowerment in cultural studies.